"Measuring up": a systematic literature review of performance measurement in Australia and New Zealand local government. Issue 2 (26th February 2021) - Johnsson, Mary C.; Pepper, Matthew; Price, Oriana Milani; Richardson, Lauren P.
Abstract : Purpose: Measurement practices have long been considered vital for informing the management of performance in organisations. Their application to local governments is a more recent, yet multi-decade phenomenon facilitated by New Public Management trends. This paper aims to review the landscape of publications that discuss performance measurement (PM) practices in Australian and New Zealand local government contexts and identify implications for future research. Design/methodology/approach: A systematic review methodology was used to identify a shortlist of publications. Next, a rating-based researcher appraisal process was applied. Multiple iterations of search and appraisal were conducted to form the basis for inductive thematic analysis and synthesis. Findings: Analysing 65 PM publications, two interrelated themes, namely, discourses of performance as efficiency, accountability or strategic growth and change were identified, which influence the adoption of local PM tools and frameworks. As demands for strategic growth and more complex service delivery increase, strategic and localised adaptation of PMs may be required to integrate learning and communicative competencies with technical and operational capabilities. Research limitations/implications: The systematic review methodology has been applied to address some of the limitations of publication and reporting biases in literature. This research provides a starting point for future investigations and broadening of discourse in local government contexts. Originality/value: This paper represents the first systematic review of 1995–2020 publications on performance management practices used by local governments in Australia and New Zealand.